2020
DOI: 10.4103/psychiatry.indianjpsychiatry_1057_20
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 on the families of first-line rescuers

Abstract: Under the COVID-19 epidemic, the families of front-line rescue workers are under unusual pressure. We aim to understand the extent of their psychological distress in this epidemic and whether they have received sufficient support. Thus targeted to provide support for them and indirectly reduce the concerns of the rescue workers. From February 27 to March 1, 2020, we used the scales of Perceived Stress Scale, 10-items Connor-Davidson Resilience Scale, Generalized Anxiety Disorder-7, Patient Health Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Furthermore, a study by Feng et al highlighted that people whose relatives were working as front-line rescue workers (eg, healthcare professionals) perceived unusual pressure and anxiety for the risks their relatives had to face during the pandemic. 34 This was also reported in our interviews, where participants seemed to be more worried about their relatives’ health than about their own. This is in contrast with what was found for other rheumatic and musculoskeletal disorders, where many patients conveyed fear about the increased risk of infection and severe health-related outcomes due to COVID-19 pandemic because of their older age, having chronic conditions, or exposure through the workplace or contact with family members.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, a study by Feng et al highlighted that people whose relatives were working as front-line rescue workers (eg, healthcare professionals) perceived unusual pressure and anxiety for the risks their relatives had to face during the pandemic. 34 This was also reported in our interviews, where participants seemed to be more worried about their relatives’ health than about their own. This is in contrast with what was found for other rheumatic and musculoskeletal disorders, where many patients conveyed fear about the increased risk of infection and severe health-related outcomes due to COVID-19 pandemic because of their older age, having chronic conditions, or exposure through the workplace or contact with family members.…”
Section: Discussionsupporting
confidence: 71%
“…The type of occupational problems to which workers were exposed changed over the course of the pandemic: in the early stages, a lack of readiness, a shortage of PPE, separation from families, stigma [ 40 ], and an increased workload [ 41 , 42 ] prevailed among professionals whereas in later stages other stressors, such as the death of patients and colleagues inducing moral injury and distress [ 43 , 44 ] and isolation or lack of support at work [ 45 , 46 ], attracted the attention of researchers. Moreover, a lack of physical activity has been associated with a poor quality of life in frontline HCWs [ 47 ], and a number of studies has underlined the importance of meditation and spirituality in improving psychological resilience in HCWs during the pandemic [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be associated with direct contact with COVID-19 patients [ [25] , [26] , [27] ]. Thus, front-line healthcare workers may have a higher risk of being infected by COVID-19, more intensive work [ 28 ], isolation from their families [ 11 , 29 ] and higher levels of COVID-19-related stress, anxiety, depression [ [30] , [31] , [32] ]. In contrast to our study, two recent meta-analyses reported slightly lower prevalence of insomnia symptoms among healthcare workers [ 10 , 33 ].…”
Section: Discussionmentioning
confidence: 99%